KUALITAS PELAYANAN KREDIT PEMILIKAN RUMAH (KPR) SUBSIDI PT. BANK TABUNGAN NEGARA (PERSERO) TBK. KANTOR CABANG BANJARBARU - WIDIATI, WIDIATI Widiati (Jurnal PubBis, 2022)
ABSTRACT Public service is one of the manifestations of the function of the state apparatus as a public servant or citizen. This research is intended to improve the quality of public services, especially in the Subsidized Home Ownership Credit (KPR) Service of PT. State Savings Bank (Persero) Banjarbaru Branch Office. The research method used in this study is a qualitative descriptive method and a data mining tool in the form of a questionnaire/questionnaire, interviews for primary data and observations and documentaries as secondary data. The informants in this study were 50 customers who were respondents in this study, and 3 credit service staff consisting of 1 Loan Service staff and 2 Loan Officer staff. The results of the research on the tangible dimension obtained a score of 48.8% (not good), the responsiveness dimension obtained a score of 54% (good enough). The dimensions of service quality that are declared good according to the interpretation of the data in service quality are in the dimensions of reliability 64% (good), assurance dimensions 70% (good), and empathy dimensions 61.4% (good). Overall, the calculation of dimensions obtained a percentage of 59.64% included in the good category seen from the interpretation of data in service quality.